2021
DOI: 10.3389/fphar.2021.743259
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Safety and Efficacy Between Clopidogrel and Ticagrelor in Elderly Patients With Acute Coronary Syndrome: A Systematic Review and Meta-Analysis

Abstract: Background: Dual antiplatelet therapy combining aspirin with a P2Y12 adenosine diphosphate receptor inhibitor is a therapeutic mainstay for acute coronary syndrome (ACS). However, the optimal choice of P2Y12 adenosine diphosphate receptor inhibitor in elderly (aged ≥65 years) patients remains controversial. We conducted a meta-analysis to compare the efficacy and safety of ticagrelor and clopidogrel in elderly patients with ACS. Methods: We comprehensively searched in Web of Science, EMBASE, PubMed, and Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In our study, >90 % of patients were taking clopidogrel, but current guidelines recommend prasugrel or ticagrelor over clopidogrel after acute coronary syndromes (ACSs) [ 1 , 73 , 74 ]; however, this recommendation is not without controversy, especially in older patients and patients with higher bleeding risks [ 75 ]. Prasugrel is often not recommended in patients >75 years old [ 1 , 74 , 75 ], and meta-analysis of RCTs in older adults found 1-year ticagrelor versus clopidogrel after ACS had no effect on composite cardiovascular death, AMI, and stroke (RR 1.04; 95 % CI: 0.69, 1.65) but was associated with an increased risk of major or minor bleeding (RR 1.40; 95 % CI: 1.11, 1.76) [ 76 ]. Among patients discharged after July 1, 2011 in our study—once all P2Y 12 inhibitors were available on the market—4.2 % took ticagrelor, 8.5 % took prasugrel, and 87.3 % took clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, >90 % of patients were taking clopidogrel, but current guidelines recommend prasugrel or ticagrelor over clopidogrel after acute coronary syndromes (ACSs) [ 1 , 73 , 74 ]; however, this recommendation is not without controversy, especially in older patients and patients with higher bleeding risks [ 75 ]. Prasugrel is often not recommended in patients >75 years old [ 1 , 74 , 75 ], and meta-analysis of RCTs in older adults found 1-year ticagrelor versus clopidogrel after ACS had no effect on composite cardiovascular death, AMI, and stroke (RR 1.04; 95 % CI: 0.69, 1.65) but was associated with an increased risk of major or minor bleeding (RR 1.40; 95 % CI: 1.11, 1.76) [ 76 ]. Among patients discharged after July 1, 2011 in our study—once all P2Y 12 inhibitors were available on the market—4.2 % took ticagrelor, 8.5 % took prasugrel, and 87.3 % took clopidogrel.…”
Section: Discussionmentioning
confidence: 99%
“…Author details 1 Senior Department of Cardiology, The Sixth Medical Center, Chinese PLA General Hospital and Chinese PLA Medical School, Beijing 100853, China. 2 Department of Geriatrics, The Second Medical Center, Chinese PLA General Hospital, Beijing 100853, China. 3 Department of Cardiology, Hainan Hospital, Chinese PLA General Hospital, Sanya 572000, Hainan, China.…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…Coronary heart disease (CHD) is the number one killer threatening human health, and the incidence increases significantly with age [1]. With the aggravation of population aging, the proportion of elderly patients hospitalized for acute coronary syndrome (ACS) is increasing, and studies showed that more than 30% of patients are over 75 years old [2,3]. The risk of bleeding and acute myocardial infarction post-percutaneous coronary intervention (re-MI) at 1-year follow-up is more than doubled in elderly patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…Dual antiplatelet therapy (DAPT) is the mainstay of pharmacotherapy for patients with ACS receiving PCI therapy [ 1 ]. Recent clinical studies have shown that ticagrelor has a better effect on the short-term prognosis of patients with ACS who undergo PCI than clopidogrel [ 6 ]. Pharmacodynamic studies have demonstrated that platelet inhibition by ticagrelor is greater and faster than that by clopidogrel [ 7 ].…”
Section: Introductionmentioning
confidence: 99%